Bodily collisions: Toward a new materialist account of memorial art. (February 2020) - Golańska, Dorota
The major objective of this article is to elaborate on the new materialist philosophical framework as a useful analytical perspective for approaching contemporary artistic memorials. The Memorial to the Murdered Jews of Europe (designed by Eisenman, 2005) and The Garden of Exile (designed by Libeskind, 2001), both situated in Berlin, serve as illustrative examples for theoretical investigations developed in this contribution. Relying on Deleuze and Guattari's definition of art, the article argues that these sites heighten our awareness of materials, compositional structures, or the process of encountering the work. By weaving together the representable (narrative/symbolic/semiotic) and the unrepresentable (traumatic/bodily/material), the sites deny a purely representational logic, producing instead intensive singular events that are never fixed or unwavering. The memorial character of these sites is therefore always emergent and contingent on the complex dynamic material-semiotic assemblages of different bodies. As such, it only exists in the encounter. Relation is its onto-epistemology.